2010
DOI: 10.1007/s00534-009-0246-8
|View full text |Cite
|
Sign up to set email alerts
|

Novel photodynamic therapy against biliary tract carcinoma using mono‐l‐aspartyl chlorine e6: basic evaluation for its feasibility and efficacy

Abstract: NPe6 PDT was effective in carcinomas even in the presence of bile, and causes no serious complication for the liver and Glisson structure. Therefore, NPe6 PDT will be a useful candidate as a new therapy for biliary tract carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…Furthermore, laserphyrin‐PDT (L‐PDT) is associated with lower skin phototoxicity compared with photofrin [13], and NPe6 is degraded rapidly in vivo and has excellent antitumor activity [12, 14]. Moreover, L‐PDT is effective in tumors even in the presence of bile, and has no serious hepatotoxicity [15]. Thus, L‐PDT is a promising treatment with higher cure rate and lower side effects than photofrin‐PDT (P‐PDT) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, laserphyrin‐PDT (L‐PDT) is associated with lower skin phototoxicity compared with photofrin [13], and NPe6 is degraded rapidly in vivo and has excellent antitumor activity [12, 14]. Moreover, L‐PDT is effective in tumors even in the presence of bile, and has no serious hepatotoxicity [15]. Thus, L‐PDT is a promising treatment with higher cure rate and lower side effects than photofrin‐PDT (P‐PDT) [16].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, hepatocytes that incorporated a large amount of Laserphyrin and bile components were impaired by Laserphyrin. However, this does not cause complications due to the regenerative ability of hepatocytes unless hemorrhage, abscess or bile congestion occurs (10). Based on the above basic experimental findings (10), liver disorders caused by Laserphyrin accumulating in hepatocytes were expected; however, based on clinical experience of radiofrequency irradiation, it was concluded that this may be avoided by adjusting the laser irradiation dose.…”
Section: Discussionmentioning
confidence: 98%
“…Japanese white rabbits were intraperitoneally anesthetized with pentobarbital sodium (Kyoritsuseiyaku Corp., Tokyo, Japan) and underwent laparotomy 4 h following the intravenous administration of Laserphyrin at 63 mg/kg, as previously described (9,10). An incision was made in the duodenum wall, and a 6 Fr sheath was inserted trans-transpapillary.…”
Section: Evaluation Of Glisson's Capsule Ensheathing the Hepatic Artementioning
confidence: 99%
See 1 more Smart Citation
“…An animal model of tumor bearing mice was established by intrahepatically implanting cells of human cholangiocarcinoma cell line NOZ to 4-week-old male BALB/c nu/nu mice [13]. In brief, the NOZ cells suspended in 100 μL of serum-free DMEM medium were inoculated subcutaneously in the back of the male nude mice.…”
Section: Determination Of Talaporfin In Sera and Tissues Of Tumor Beamentioning
confidence: 99%